2010
DOI: 10.1103/physreva.82.012704
|View full text |Cite
|
Sign up to set email alerts
|

Absolute cross sections for electron loss, electron capture, and multiple ionization in collisions ofC3+with noble gases

Abstract: Absolute charge-state-correlated cross sections for projectile electron loss, electron capture, and target multiple ionization in collisions between C 3+ ions and noble gases have been measured for energies between 1.3 and 3.5 MeV. The data have been compared with other similar absolute cross sections existent in the literature for several projectiles. Calculations for the single-loss−multiple-ionization channel have been performed for the screening mode, using both an extended version of the classical-impulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 81 publications
9
49
0
Order By: Relevance
“…Electron-loss cross sections have been measured for atomic targets ranging from helium to xenon [5][6][7][8][9][10][11][12][13][14]. These studies have shown that for lighter targets, typically meaning for Z T < 10, where Z T is the target nuclear charge, the cross sections increase rapidly, e.g., approximately as Z n T , where n ∼ 1.4-1.7.…”
Section: Target Scaling: Experimental Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Electron-loss cross sections have been measured for atomic targets ranging from helium to xenon [5][6][7][8][9][10][11][12][13][14]. These studies have shown that for lighter targets, typically meaning for Z T < 10, where Z T is the target nuclear charge, the cross sections increase rapidly, e.g., approximately as Z n T , where n ∼ 1.4-1.7.…”
Section: Target Scaling: Experimental Overviewmentioning
confidence: 99%
“…More recently, Santos et al [7,26] further explored these concepts and used C 3+ and He + data to determine the ratio σ anti /σ e , which combined with the impulse approximation, enabled them to estimate the average number of active target electrons for the antiscreening mode. This was done as a function of collision energy and fitted to…”
Section: Overview Of Theoretical Models and Comparison With Expementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that the multiple ionization of rare gas targets in collision with ions has been extensively investigated over the past several decades, 1 it still continues to pose experimental [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and theoretical challenges. 13,[16][17][18][19][20] For example, studies focused on the comparison between bare or partially stripped ions shed light on the role of the projectile effective charge state in direct multiple ionization processes of rare noble gases.…”
Section: Introductionmentioning
confidence: 99%
“…3,8,9,15,21 We illustrate the method presenting measurements of ionization of helium atom, resulting from collisions with C 3 + ions. In order to check the accuracy of our method, we compare our results to the works of Santos and co-workers, 2 where a time of flight spectrometer inside a gas cell target was used to study the collision between C 3 + and rare gas atoms. We also extend their measurements from 3.5 MeV to 5 MeV.…”
Section: Introductionmentioning
confidence: 99%